Pathways to adolescent male violent offending - Ashton, Sally-Ann (Routledge studies in criminal behaviour, 2023)
"This book differentiates between categories of adolescent male offending and explores the behavioural and social profiles of those who become involved in violent offending and organized crime. Using self-reported and arrest data, the book examines key stages of male adolescent offending with a view to early recognition of behaviours that leave young men vulnerable to criminal exploitation and the escalation of violence. It also explains the importance of understanding crime motivations, how young men view themselves when they offend, and the emotions that they experience. Rather than looking at violent offending as a single category of behavior, the book helps readers differentiate between types of adolescent violence and to understand the underlying psychological and social causes. It offers an insight into the journey of young people who are criminally exploited and those who become involved in committing acts of serious violence and organized crime. It does so by using data from official records, self-reported offending, and the narratives of young people. Each chapter focuses on a particular stage of offending with a view to early identification, support, and diversion. Pathways to Adolescent Male Violent Offending is aimed at practitioners in youth offending services, youth work, policing, and education. It will also be useful for students of forensic and investigative psychology, criminal justice, policing, and child and adolescent mental health"--